Konversi Agama dalam Perdebatan Akademis - Dianto, Icol (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2022)
AbstractThis research aims to analyze the phenomenon of religious conversion in theory and practice. This research uses library research in answering two main questions, namely how is the academic debate and case study of conversion of Islam and Christianity? The authors found that the factors that influence the process of religious conversion are caused by internal factors in the individual such as frustration, soul shocks, damaged souls and spiritual experiences. External factors such as the influence of the social environment, organization, peers, and marriage. This academic debate about religious conversion has started from William James (1958) with the theory of conversion as the healing of a divided self until Henri Gooren (2010) with the theory of the conversion career. Finally, the case of religious conversion to Islam is not through mental disorders, violence and coercion, but with full awareness. However, converts to Christianity are often followed by cases of violence, coercion, and mental disorders. Keywords: Religious conversion, Conversion Career. AbstrakPenelitian ini bertujuan untuk menganalisis fenomena konversi agama dalam teori dan praktik.  Penelitian ini menggunakan library research dalam menjawab dua pertanyaan pokok, yaitu bagaimana perdebatan akademis dan studi kasus konversi agama Islam dan Kristen? Penulis menemukan bahwa faktor-faktor yang mempengaruhi proses konversi agama disebabkan oleh faktor-faktor internal dalam diri individual seperti frustasi, guncangan jiwa, jiwa yang rusak dan pengalaman spiritual. Adapun faktor eksternal seperti pengaruh lingkungan sosial, organisasi, teman sejawat, dan perkawinan. Perdebatan akademis tentang konversi agama ini telah mulai sejak masa William James (1958) dengan teori Conversion as the Healing of a Divided Self sampai Henri Gooren (2010) dengan teori The Conversion Career. Terakhir, kasus konversi agama ke Islam tidak melalui gangguan-gangguan mental, kekerasan dan pemaksaan, namun dengan kesadaran penuh. Namun, pelaku konversi agama ke Kristen seringkali diikuti oleh kasus-kasus kekerasan, pemaksaan, dan gangguan mental. Kata kunci: Konversi agama, Karier konversi.